2016
DOI: 10.1186/s13024-016-0129-9
|View full text |Cite
|
Sign up to set email alerts
|

A Christianson syndrome-linked deletion mutation (∆287ES288) in SLC9A6 disrupts recycling endosomal function and elicits neurodegeneration and cell death

Abstract: BackgroundChristianson Syndrome, a recently identified X-linked neurodevelopmental disorder, is caused by mutations in the human gene SLC9A6 encoding the recycling endosomal alkali cation/proton exchanger NHE6. The patients have pronounced limitations in cognitive ability, motor skills and adaptive behaviour. However, the mechanistic basis for this disorder is poorly understood as few of the more than 20 mutations identified thus far have been studied in detail.MethodsHere, we examined the molecular and cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
61
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 129 publications
(169 reference statements)
7
61
1
Order By: Relevance
“…[49][50][51] In animals, maternal preconceptual opioid exposure is associated with altered sex-specific behavioral outcomes in both the first and second generations. 56 Although we do not wish to over interpret our results, we will have not yet been validated in the literature also show involvement in the pathogenesis of neurodevelopmental disorders (SLC9A6, 84,85 PPP1R15B 86 are associated with intellectual disability 87 ). 56 Although we do not wish to over interpret our results, we will have not yet been validated in the literature also show involvement in the pathogenesis of neurodevelopmental disorders (SLC9A6, 84,85 PPP1R15B 86 are associated with intellectual disability 87 ).…”
Section: Moud Associated With Altered Fce Protein Cargo: Pilot Analmentioning
confidence: 86%
See 1 more Smart Citation
“…[49][50][51] In animals, maternal preconceptual opioid exposure is associated with altered sex-specific behavioral outcomes in both the first and second generations. 56 Although we do not wish to over interpret our results, we will have not yet been validated in the literature also show involvement in the pathogenesis of neurodevelopmental disorders (SLC9A6, 84,85 PPP1R15B 86 are associated with intellectual disability 87 ). 56 Although we do not wish to over interpret our results, we will have not yet been validated in the literature also show involvement in the pathogenesis of neurodevelopmental disorders (SLC9A6, 84,85 PPP1R15B 86 are associated with intellectual disability 87 ).…”
Section: Moud Associated With Altered Fce Protein Cargo: Pilot Analmentioning
confidence: 86%
“…have not yet been validated in the literature also show involvement in the pathogenesis of neurodevelopmental disorders (SLC9A6, 84,85 PPP1R15B 86 are associated with intellectual disability 87 ). Upregulated miRs of interest in the buprenorphine-exposed group include miR 10b-5p, miR 10a-5p, miR 183-5p and miR 182-5p and alter the expression of molecules known to modulate synaptic plasticity that also contribute to the etiology of psychiatric diseases.…”
Section: Moud Associated With Altered Fce Protein Cargo: Pilot Analmentioning
confidence: 99%
“…Thus in CS, it has been postulated that defects in NHE6 will compromise endosomal pH homeostasis and cargo trafficking in many tissues, but especially the CNS, leading to pleiotropic pathophysiological disturbances. This is supported by studies of mouse hippocampal neurons where disruption of NHE6 expression resulted in overacidification of early and recycling endosomes and diminished signalling from the tropomyosin or tyrosine receptor kinase B (TrkB) (33) and the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor (53,54) that correlated with reduced neurite outgrowth and branching, synapse density and maturation, and circuit strength.…”
mentioning
confidence: 88%
“…To empirically visualize and evaluate the functional significance of the individual variants, we engineered them into the WT human NHE6 cDNA that was fused at its Cterminus to either enhanced green fluorescent protein (GFP), monomeric Cherry fluorescent protein (ChFP) or influenza hemagglutinin (HA)-epitope (NHE6GFP, NHE6ChFP, or NHE6HA respectively). We previously showed that the molecular and cellular properties of these chimeric constructs were indistinguishable from unmodified NHE6 when examined in AP-1 cells, a Chinese hamster ovary-derived cell line lacking detectable levels of endogenous NHE6 and therefore serves as a useful cell model system to study this transporter (53).…”
Section: Biosynthetic Maturation and Stability Of The Nhe6 Variantsmentioning
confidence: 99%
See 1 more Smart Citation